Legalisasi Pekerja Seks Komersial dalam Perspektif Hukum, Etika, dan Moralitas - Wicaksono, Emirza Nur (Journal of Law & Policy Review, 2025)
This study examines the legalization of commercial sex work as a form of employment from legal, ethical, and moral perspectives in Indonesia. The purpose of this research is to analyze the existing legal framework governing sex work, assess the social, legal, and moral implications of legalization, and formulate an ideal legal policy aligned with the nation’s humanitarian and moral principles. This research employs a normative juridical approach through literature studies on statutory regulations, legal doctrines, and ethical as well as moral considerations. The findings indicate that current regulations have not effectively protected sex workers, while society continues to emphasize moral and ethical values. The legalization of sex work can be justified under the principles of human rights protection, strict social supervision, and economic empowerment. The ideal legal policy formulation should emphasize a humanistic, participatory, and moderate regulatory framework, ensuring that sex work practices are governed without neglecting national ethics and morality.